Sindroma Sheehan dengan Hiponatremia Berulang, Miositis dan Amenorrhea Sekunder - Luse Loe; Nanny Natalia Mulyani Soetedjo; Hikmat Permana (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: Sheehan syndrome may arise after giving birth, which is caused by reduced pituitary perfusion due to low blood pressure during or after parturition. It has varied and unspecific symptoms. Early diagnosis and treatment is important to prevent death. Case report: We reported a case of 39 years old female with recurring hyponatremia, myositis and secondary amenorrhea, which were consistent with sheehan syndrome.Discussion: Patient had history of severe postpartum bleeding. She presented with hyponatremia, hypokalemia, and hypokalemia. This electrolyte imbalance might be caused by anterior pituitary hormones deficit, possible posterior pituitary hormones deficit, disturbance of adrenocortical and estrogen hormone. Increased creatinine kinase showed myositis, and possibly caused by herbal medication or other condition.Conclusion: In this case, the patient was getting well after given adequate electrolyte and hormone replacement, without steroid administration.